Effect Of Motivation And Appreciation Of Employee Performance At The Department Of Transportation Makassar - A. afifah ramadani; Sitti Marhumi; Muhammad Akib (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine the effect of motivation and rewards on employee performance at the Makassar City Transportation Agency. This study uses a quantitative method with a multiple linear regression approach. Data were collected through questionnaires distributed to 89 employees. The results of the study indicate that motivation has a significant effect on employee performance with a T value (T-statistic) of 7.523 and a significance level of 0.000. Rewards also have a significant effect on employee performance with a T value (T-statistic) of 2.359 and a significance level of 0.021. The T value (T-statistic) in this context is a test statistic used to determine whether the coefficient of the independent variable (motivation and rewards) is significantly different from zero, which means that the variable has an effect on the dependent variable (employee performance). A higher T value indicates that the independent variable has a strong and significant effect. In addition, the combination of motivation and rewards explains 60.8% of the variation in employee performance, as indicated by the R Square value of 0.608. The conclusion of this study is that motivation and rewards play an important role in improving employee performance. Therefore, it is recommended to improve motivation programs and reward systems to achieve optimal performance.